Rencana Program Rehabilitasi Sosial Anak Yang Terpapar Radikalisme Melalui Perubahan Karakter Di Sentra Handayani Jakarta - Sri Sulistyaningsih (BADAN PENERBIT STIEPARI PRESS, 2023)
Changing the character of children who are exposed to radicalism is one of the efforts made by the government, in this case, one of which is carried out by the Sentra Handayani. The aim is to change the character of children who are victims of families who are closely related to acts of radicalism. The efforts made are through the Social Rehabilitation Program with psychosocial guidance, national guidance, physical guidance and group dynamics which are carried out by officers at the Handayani Center. This research was conducted with a qualitative method and descriptive type. The power collection techniques are in the form of observation, documentation studies and in-depth interviews with the sampling technique namely purposive sampling. The results of this study are that social rehabilitation programs that are carried out intensively and maximally are able to change the character of children who are exposed to radicalism to become better characters than before.